2016
DOI: 10.1007/s10661-016-5514-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry and quality of surface water and groundwater in the vicinity of Lake Monoun, West Cameroon: approach from multivariate statistical analysis and stable isotopic characterization

Abstract: With the use of conventional hydrogeochemical techniques, multivariate statistical analysis, and stable isotope approaches, this paper investigates for the first time surface water and groundwater from the surrounding areas of Lake Monoun (LM), West Cameroon. The results reveal that waters are generally slightly acidic to neutral. The relative abundance of major dissolved species are Ca(2+) > Mg(2+) > Na(+) > K(+) for cations and HCO3 (-) ≫ NO3 (-) > Cl(-) > SO4 (2-) for anions. The main water type is Ca-Mg-HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…It indicates that most of the samples belong to the kaolinite stability field, demonstrating that kaolinite is the most stable secondary phase for the waters in the study area. This result is consistent with what has been reported by some authors [7,28,31,39,40] under humid tropical climatic conditions. Kaolinite constituted the main clay mineral formed through the monosiallitization process, which characterizes the humid tropical zone [45].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It indicates that most of the samples belong to the kaolinite stability field, demonstrating that kaolinite is the most stable secondary phase for the waters in the study area. This result is consistent with what has been reported by some authors [7,28,31,39,40] under humid tropical climatic conditions. Kaolinite constituted the main clay mineral formed through the monosiallitization process, which characterizes the humid tropical zone [45].…”
Section: Discussionsupporting
confidence: 94%
“…The compositional relations between the dissolved ions (Table 6) were computed using stoichiometric relations. The (Ca + Mg)/total cations ratios of all the samples varied from 0.36 to 0.75, with 83% of the values higher than 0.5, implying a high contribution of Ca 2+ and Mg 2+ in cations [28,50]. Further, the plot of (Ca + Mg) versus total cations for all the water samples (Figure 6a) showed that the whole points were below the 1:1 line, suggesting a contribution from the weathering reactions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rajah 6 menunjukkan korelasi yang baik antara nilai kekonduksian dan nilai jumlah pepejal terlarut bagi sampel air di kawasan kajian. Menurut Kamtchueng et al (2016), nilai-nilai ini menunjukkan keadaan air bawah tanah yang secara relatifnya adalah muda serta mempunyai tindakbalas kimia yang terhad dengan batuan akuifer dominan silika di kawasan kajian. Selain itu, ia menggambarkan kepelbagaian proses hidrokimia yang berlaku di dalam air bawah tanah di kawasan Selangor ini.…”
Section: Analisis Kimia Air Bawah Tanahunclassified
“…Hydrogeochemical processes help to unravel changes in surface water quality relating to water-rock interaction or anthropogenic impacts (Singh et al 2005;Kumar et al 2006;Franz et al 2014;Nganje et al 2015;Kamtchueng et al 2016). The geochemical properties of surface water also depend on the chemistry of the recharging source as well as the various geochemical processes occurring within the drainage basin.…”
Section: Introductionmentioning
confidence: 99%